ΑΝΑΣΥΓΚΡΟΤΩΝΤΑΣ ΤΗΝ «ΚΟΙΝΟΤΗΤΑ» ΣΤΙΣ ΒΕΝΕΤΟΚΡΑΤΟΥΜΕΝΕΣ ΕΛΛΗΝΙΚΕΣ ΠΕΡΙΟΧΕΣ. ΟΡΓΑΝΩΣΗ ΚΑΙ ΑΡΧΕΙΑΚΕΣ ΠΗΓΕΣ - ΠΑΠΑΔΙΑ-ΛΑΛΑ ΑΝΑΣΤΑΣΙΑ (Eoa kai Esperia, 2007)
This paper, which brought to an end the One-day Conference, titled"Greek Communities and the European World (13th-19th centuries). Patternsof self-administration, social organization, identities’ formation", attempts tosynthesize and summarize the conclusions of the research programme of thesame name, with an emphasis on communities in Greek lands under Venetianrule. These communities are approached as a factor in the formation of socialclasses and as the driving force behind the development of forms of regionalself-governing. The programme concluded that the communities were linkedto Europe via the rule of Venice, while their ’Greekness’ relates both to theGreek lands as a whole, despite border variations, and to their members, the"Greci", considerable numbers of whom were to gradually acquire positionsof note in the communities alongside their Latin overlords. The research team identified, catalogued and digitized a mass of historicalmaterial, the three most important sources of which were the embassies, theregisters of marriages and births/deaths and the communities’ statutes. Thishistorical material, which is now held at the University of Athens, alsoconstituted the main source for the synthesizing studies published in thisvolume. The material will also be available to the community of historians forfuture study and will play its part in furthering university research andteaching.